Fa‘āliyyatu Istikhdāmi al-Infūghrāfīk fī Tanmiyati Isti‘ābi Qawā‘idi an-Naḥwi li al Ṭullābi - Muqit, Abdul; Alamsyah, Muhammad (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2026)
This study aims to examine the effectiveness of infographic-based instructional media in enhancing students’ understanding of Arabic grammar rules. Employing a quantitative approach with a quasi-experimental design, this study involved two eighth-grade classes at Dar al-Istiqamah Islamic Boarding School during the 2025/2026 academic year. The experimental group (n = 13) received infographic-based instruction, while the control group (n = 14) underwent conventional instruction. Data collected via pre- and post-tests, observations, interviews, and documentation were analyzed using IBM SPSS Statistics 25. The findings revealed a statistically significant difference between the post-test scores of the two groups, demonstrating that students taught with infographic-based media achieved significantly higher grammar comprehension than those in the conventional group. These results suggest that infographic-based media effectively reduce cognitive load by presenting structured, visual linguistic information, offering a scalable solution for educators to modernize nahw pedagogy in traditional religious educational settings.